2015
DOI: 10.1159/000430867
|View full text |Cite
|
Sign up to set email alerts
|

Mood Stabilizers and the Influence on Global Leukocyte DNA Methylation in Bipolar Disorder

Abstract: Little is known about the relationship between treatments for bipolar disorder (BD), their therapeutic responses and the DNA methylation status. We investigated whether global DNA methylation levels differ between healthy controls and bipolar patients under different treatments. Global DNA methylation was measured in leukocyte DNA from bipolar patients under lithium monotherapy (n = 29) or combination therapy (n = 32) and from healthy controls (n = 26). Lithium response was assessed using the Alda scale. Lithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Although the evidence is still very limited, it has been suggested that different mood stabilizers may exert specific effects on the epigenome. Lithium monotherapy has been shown to induce global DNA hypomethylation in leuokocytes, whereas a combination therapy including VPA has been associated with hypermethylation [49]. Very few studies have investigated the extent to which methylation and histone modifications might affect the interindividual response to mood stabilizers.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Although the evidence is still very limited, it has been suggested that different mood stabilizers may exert specific effects on the epigenome. Lithium monotherapy has been shown to induce global DNA hypomethylation in leuokocytes, whereas a combination therapy including VPA has been associated with hypermethylation [49]. Very few studies have investigated the extent to which methylation and histone modifications might affect the interindividual response to mood stabilizers.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Very few studies have investigated the extent to which methylation and histone modifications might affect the interindividual response to mood stabilizers. The only study comparing differences in global DNA methylations levels in responders and non-responders to lithium treatment suggested that the observed epigenetic effects could be independent from the clinical response to the drug [49]. Although intriguing, the hypothesis that response to mood stabilizers may be associated with specific epigenetic signatures still needs to be explored by studies performed on large samples of patients and taking potential confounders into account.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…In a study of global DNA methylation in the leukocytes of BD patients, no differences were found compared to the healthy control. However a significantly lower DNA methylation level was observed in patients on lithium monotherapy, compared to controls or BD patients treated with a combination of lithium + VPA [ 82 ]. In this study, the DNA methylation level could not be correlated with the lithium response as assessed with the Alda scale.…”
Section: Dna Methylation Modifications and Responses To Treatment mentioning
confidence: 99%